Níveis de anticorpos para arbovírus em indivíduos da região de Ribeirão Preto, SP (Brasil) Arbovirus antibody levels in the population of the Ribeirão Preto area, S.Paulo State (Brazil) - Luiz Tadeu Moraes Figueiredo; Amélia P.A. Travassos da Rosa; Adhemar Mário Fiorillo (Universidade de São Paulo, 1986)
Com o objetivo de conhecer os níveis de anticorpos para arbovírus, foram estudados 302 indivíduos da região de Ribeirão Preto (Brasil), moradores em 3 tipos de locais com distintas formas de organização do espaço: próximos à área de paisagem natural; com paisagem modificada para a agropecuária; comunidades urbanas. Foram efetuados testes sorológicos de inibição da hemaglutinação, neutralização e fixação do complemento para 21 arbovírus. Os resultados mostraram que 19,9% dos indivíduos investigados apresentaram anticorpos, sugerindo infecções pregressas por vários arbovírus. A maior percentagem de habitantes que se infectaram por estes agentes foi observada em locais próximos à área de paisagem natural, 38,5%. O vesiculovírus Piry foi o agente para o qual se encontrou o maior número de soros reagentes, 12,5%. A maior ocorrência de portadores de anticorpos para o vírus Piry foi observada nos indivíduos: do sexo masculino; com idade superior a 40 anos; guardas-florestais, lavradores e profissionais com atividades ligadas ao rio. The area of Ribeirão Preto is located in the north of S.Paulo State - Brazil. The population is 611,742. The climate is sub-tropical warm and humid. The area of Ribeirão Preto is almost completely deforested and covered by extensive plantations of sugar cane and coffee and pasture. With the purpose of discovering the arbovirus antibody levels, a serologic survey was carried out among people of the Ribeirão Preto area living in different geographical environments. Fifty two inhabitants located close to natural landscap, 38 in places with landscape modified by agriculture and cattle raising, and 93 in urban communities were studied. Serologic tests for hemagglutination inhibition by 20 Togaviridae and Bunyaviridae arbovirus, and neutralization and complement fixation tests on Piry Rhabdoviridae were carried out. It was discovered that 19.9% of the sample population presented antibodies against arbovirus. The Flavivirus Togaviridae antibodies were the most frequent among inhabitants from urban communities (8.5%). Anti amarilic vaccination, carried out 8 years ago, explains this fact. Piry Rhabdoviridae obtained 12.5%, the most significant population in proportion of antibodies detected. Thirty two percent of inhabitants in a place close to natural landscape, 11.5% of inhabitants in places with landscape modified by agriculture and cattle raising, and 7,5% of inhabitants in urban communities presented Piry antibodies. This virus has never before been discovered in the south of Brazil. The highest risk of infection by Piry virus was found in men, especially older than forty: agricultural workers, forestry wardens and river workers. These conclusions are typical of a virus related to a natural environment. Geographical space is changeable, and organized according to the characteristics of a civilization at a particular point in time. The geographical space approach is more advantageous than a purely ecological view on zoonoses research in populated and organized areas in the south of Brazil.